Variation of Electrical Resistivity During Magnetic Field-Induced Martensitic Transformation in Vanadium added NiMnSnB alloys - Kırat, Gökhan (Fırat Üniversitesi, 2023)
In this study, the structural and electrical properties of Ni49-xVxMn37Sn12B2 (x = 0, 1, 2, and 3) ferromagnetic shape memory alloys were investigated. According to XRD analyzes at room temperature, the x=0 sample was in the martensite phase, the x=1 and 2 samples were in the mixture phase, and the x=3 sample was in the austenite phase. The resistivity analyses depend on temperature showed that all samples exhibited martensitic transformation and the phase transformation temperature decreased with V doping. Magnetoresistance (MR) values were calculated using ?-T curves performed under 0 T and 1 T magnetic fields. The observed negative MR is consistent with Kataoka's s-d model. As-Af interval was determined and M-H measurements were made at constant temperatures determined in this interval. The results were attributed to the magnetic field-induced phase transformation (MFIPT). In order to examine the effects of MFIPT on the electrical resistivity, the resistivity depend on magnetic field was measured using the same thermal process. The overlapping of the curves in the high magnetic field revealed that the resistivity decreased due to the MFIPT as well as the MR.